Preparation of ultrafine LiTaO3 powders by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of Li(NO3), TaF5 and citric acid in stoichiometric ratio was heated in a water bath. This gel on decomposition at 700 degrees C produced fine crystallites of ternary oxide, LiTaO3 (LT). The phase contents and lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction